Immobilized materials for removal of toxic metal ions from surface/groundwaters and aqueous waste streams. Issue 4 (5th April 2016) - Zawierucha, Iwona; Kozlowski, Cezary; Malina, Grzegorz
Abstract : Immobilized materials can be potential remediation agents for the elimination of toxic metal ions from polluted streams. Abstract : Heavy metals from industrial processes are of special concern because they produce chronic poisoning in the aquatic environment. More strict environmental regulations on the discharge of toxic metals require the development of various technologies for their removal from polluted streams ( i.e. industrial wastewater, mine waters, landfill leachate, and groundwater). The separation of toxic metal ions using immobilized materials (novel sorbents and membranes with doped ligands), due to their high selectivity and removal efficiency, increased stability, and low energy requirements, is promising for improving the environmental quality. This critical review is aimed at studying immobilized materials as potential remediation agents for the elimination of numerous toxic metal ( e.g. Pb, Cd, Hg, and As) ions from polluted streams. This study covers the general characteristics of immobilized materials and separation processes, understanding of the metal ion removal mechanisms, a review of the application of immobilized materials for the removal of toxic metal ions, as well as the impacts of various parameters on the removal efficiency. In addition, emerging trends and opportunities in the field of remediation technologies using these materials are addressed.